Meningkatkan Perekonomian Warga Sekitar Jembatan Suroboyo Berdasarkan Analisa Sosial - Nany Suryawati; Jonathan Acel Fabianrico; Amelia Andrianti Sudiyanto; Lia Nurlika; Andreas Therius Risadi; Andre Ronaldo Hariyanto (LPPM UNINUS, 2019)
Surabaya is one of the largest metropolitan cities in Indonesia and center of the economy. But Surabaya is no less interesting in terms of tourism. Surabaya has a tour of Kenjeran Beach which in recent years has become very developed, and is likely to be a promising tourism sector. Among the beauty of Kenjeran Beach, certainly not all feel it. Residents who live around Kenjeran Beach for example, in the Sukolilo area, Lor, they complain that their economic life is always below the average. Problems arise, namely the various businesses that are less attractive to visitors or customers. The UKDC students who pay attention to this issue feel the need for change to improve the economy of the surrounding community so as to provide counseling in the form of masks, gloves, and haircap to maintain hygiene of processed products and the importance of hygiene in production, teaching the use of more simple and trendy plastic packaging for souvenir food, give a sticker in the form of a business logo that can be affixed to a ziplock plastic, teach how to shop online by using Go-Pay at the place of business, and give a signboard to the local RT and RW. After 3 months training, the place of business experienced an increase in sales, there was a new income from Go-Pay, a place of business that used to only be crowded with adults, is now beginning to expand to teenagersSurabaya is one of the largest metropolitan cities in Indonesia and center of the economy. But Surabaya is no less interesting in terms of tourism. Surabaya has a tour of Kenjeran Beach which in recent years has become very developed, and is likely to be a promising tourism sector. Among the beauty of Kenjeran Beach, certainly not all feel it. Residents who live around Kenjeran Beach for example, in the Sukolilo area, Lor, they complain that their economic life is always below the average. Problems arise, namely the various businesses that are less attractive to visitors or customers. The UKDC students who pay attention to this issue feel the need for change to improve the economy of the surrounding community so as to provide counseling in the form of masks, gloves, and haircap to maintain hygiene of processed products and the importance of hygiene in production, teaching the use of more simple and trendy plastic packaging for souvenir food, give a sticker in the form of a business logo that can be affixed to a ziplock plastic, teach how to shop online by using Go-Pay at the place of business, and give a signboard to the local RT and RW. After 3 months training, the place of business experienced an increase in sales, there was a new income from Go-Pay, a place of business that used to only be crowded with adults, is now beginning to expand to teenagers.